2012
DOI: 10.1080/02755947.2012.705258
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Equilibrium Walleye Population Density under Static and Dynamic Recreational Angling Effort

Abstract: Understanding the dynamics of angling effort and how fish populations are affected by angler effort is an important and often unappreciated component of fisheries management. Our objective was to determine the extent to which angling‐induced mortality limits walleye Sander vitreus population density in northern Wisconsin lakes. We developed a simulation model to evaluate the effects on long‐term equilibrium walleye population density caused by effort limitations, density‐dependent angling effort, and angling r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
1
7
1
Order By: Relevance
“…However, the numerical response of anglers to fish abundance is equally important in understanding whether the interaction between fish abundance and harvest is likely to be sustainable (Schueller et al 2012;Allen et al 2013;Askey et al 2013). Typically there is a positive relationship between fish abundance and angler effort (e.g., Post et al 2008;Schueller et al 2012), yet we observed no significant relationship in this study. It is not clear why there is a lack of correlation in our study, but it could be partially due to differential access or travel costs between lakes .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…However, the numerical response of anglers to fish abundance is equally important in understanding whether the interaction between fish abundance and harvest is likely to be sustainable (Schueller et al 2012;Allen et al 2013;Askey et al 2013). Typically there is a positive relationship between fish abundance and angler effort (e.g., Post et al 2008;Schueller et al 2012), yet we observed no significant relationship in this study. It is not clear why there is a lack of correlation in our study, but it could be partially due to differential access or travel costs between lakes .…”
Section: Discussioncontrasting
confidence: 55%
“…It is not clear why there is a lack of correlation in our study, but it could be partially due to differential access or travel costs between lakes . The lack of a relationship between angler effort and fish abundance can be a concern for the sustainability of wild stock fisheries (Walters and Martell 2004;Schueller et al 2012;Allen et al 2013), although the lakes in this study are maintained by stocking. If angler effort does not respond to changes in fish abundance, then the possibility for overfishing exists if angler effort remains high as fish abundance declines.…”
Section: Discussionmentioning
confidence: 97%
“…Others have even suggested that recreational fisheries may self‐regulate (Pereira & Hansen ; Schueller et al . ). Coupled angling effort responses to fish abundance have also commonly been assumed in some modelling simulations studying recreational fisheries (Johnston et al .…”
Section: Introductionmentioning
confidence: 97%
“…The strength of relationships between recreational angling effort and fish abundance has been the subject of relatively few studies of which some have shown apparent strong relationships between effort and fish abundance Post et al 2008). Others have even suggested that recreational fisheries may self-regulate (Pereira & Hansen 2003;Schueller et al 2012). Coupled angling effort responses to fish abundance have also commonly been assumed in some modelling simulations studying recreational fisheries (Johnston et al 2010;van Poorten et al 2011;Allen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Angler effort restrictions may represent an important management option for maintaining rainbow trout in the LBR. Active management policies that seek to reduce fishing effort are often socially unacceptable (Schueller et al 2012) and hence have rarely been implemented in inland recreational fisheries (Pereira and Hansen 2003). An approach that has been implemented with success, albeit in big-game wildlife management systems, is access limitation via lottery systems (Boxall 1995;Scrogin et al 2000).…”
Section: Discussionmentioning
confidence: 99%